The human development index adjusted for efficient resource utilization - F. J. Arcelus; B. Sharma; G. Srinivasan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
The human development index (HDI) developed by the United Nations Development Programme is computed as the average of three equally weighted outcome measures: life expectancy (LI), educational attainment (EI) and income (WI). However, this computational process is independent of the resources being devoted by each country to the achievement of the three outcome levels. Hence, it is conceivable that two different countries may consume vastly different amount of resources in achieving the same outcome, say, LI. However, this difference in the efficiency of resource utilization is not reflected in the HDI. The purpose of this paper is to address this efficiency issue.
Keywords: C10; I31; 330; human development index; data envelopment analysis; efficiency; congestion and scale economics; Entwicklungsindikator